2009
DOI: 10.1089/ten.tea.2008.0345
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Metabolism, and Growth Inhibitors of Mesenchymal Stem Cells

Abstract: Most therapeutic applications of bone marrow stromal cells (MSCs), or mesenchymal stem cells, require expansion of these cells. This study aimed to obtain more information about human MSCs regarding their expansion characteristics: growth, metabolism, and growth inhibitors. In addition, the same expansion factors were examined for (model species) goat and rat MSCs to evaluate differences between MSCs of mammalian species. MSC proliferation, nutrient consumption, and metabolite production were determined for fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
176
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(195 citation statements)
references
References 31 publications
17
176
2
Order By: Relevance
“…Growth, oxygen and glucose consumption kinetics were determined by fitting of the model parameters to the experimental data. Glutamine wasn't considered since it is an unimportant energy source for hMSC [16]. The modeled curves for a 60 cm 3 scale are exemplarily shown in Figure 7.…”
Section: Cultivation In Different Scales -Consumption and Growth Kinementioning
confidence: 99%
See 1 more Smart Citation
“…Growth, oxygen and glucose consumption kinetics were determined by fitting of the model parameters to the experimental data. Glutamine wasn't considered since it is an unimportant energy source for hMSC [16]. The modeled curves for a 60 cm 3 scale are exemplarily shown in Figure 7.…”
Section: Cultivation In Different Scales -Consumption and Growth Kinementioning
confidence: 99%
“…The growth and consumption rates are comparable to those reported in the literature. Glucose consumption and growth rates of human mesenchymal stem cells are referred to be (0.23 -1.22) x 10 -7 mg/h/cell [17,18] and 0.33 -0.94 1/d [15,16,[19][20][21][22], respectively. Oxygen consumption rates of (1.22 -3.20) x 10 -8 mg/h/cell are reported for various human cell types [23][24][25][26][27].…”
Section: Cultivation In Different Scales -Consumption and Growth Kinementioning
confidence: 99%
“…Yet, if we tentatively set 75% as the threshold, the tolerant concentrations for both L-lactic acid and L,D-lactic acid are between 10-20 mmol/L according to our examinations of rat MSCs, and additions of 40 mmol/L lactic acids resulted in decrease of ALP activity more than 50% relative to the blank control ( Figure 6). In a previous study of growth inhibitors including lactic acids (lack of the groups of medium pH, salt, lactate, and D,L-lactic acids), Schop et al [44] indicated the cell-type dependence of the response to L-lactic acids: rat MSCs was inhibited at 16 mmol/L and human MSCs at 35.4 mmol/L. So, human cells are more tolerant to lactic acids.…”
Section: Is There Any Significant Difference Of Cytotoxicity Between mentioning
confidence: 99%
“…How to decouple these three factors and determine the main one is an important topic, although some single factors have been examined [43,44]. Another fundamental question is the possible difference of cell responses between the two optical isomers of lactic acids.…”
mentioning
confidence: 99%
“…Glucose and lactate concentrations in supernatants were determined using an YSI 2700 automated analyser (Yellow Springs Instruments). Generation time (t d , days), cell growth rate (l, days -1 ), specific consumption (q Glc , nmol/10 6 cells/h) and production rates (q lac , nmol/10 6 cells/h) of extracellular metabolites (glucose and lactate, respectively) were calculated as described elsewhere (Schop et al 2009). ASC, MSC and chondrocyte progenitors were cultured in low glucose DMEM medium supplemented with streptomycin (0.167 g/L, SigmaAldrich), kanamycin (0.075 g/L, Sigma-Aldrich) and 10 % FCS.…”
mentioning
confidence: 99%